Strategic Planning of Morotai Tourism Village Information System (SIDEWITA) Using Ward and Peppard Method - Yerik Afrianto Singgalen (Journal of Information System and Informatics, 2023)
This study explores how digital literacy in Indonesia has stimulated the development of a website-based information system used for digital marketing. The Morotai Island district, identified as a priority tourism destination, has been optimized as a superior product with the help of communication technology infrastructure and internet networks based on the innovative city concept. This optimization has triggered collaboration among individuals, communities, and stakeholders in the tourism sector, resulting in superior tourism products in each destination. To facilitate collaboration, the Morotai Tourism Village Information System (SIDEWITA) is proposed to connect individual, community, and stakeholder interests. This study applies the Ward and Peppard framework, including Value Chain Analysis, PEST, SWOT, and McFarlan Strategic Grid, to analyze internal and external conditions for SIDEWITA's strategic planning.